CONSIDERATIONS OF ISLAMIC EDUCATION PHILOSOPHY: THE PAST AND THE FUTURE - Safuroh; Rasad Mulyadi; Devi Fatwanti; Wasehudin; Erdi Rudjikartawi; Agus Gunawan (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to analyze the philosophical considerations of Islamic education in the past, the problems of Islamic education today, and the challenges of Islamic education in the future. The approach used is descriptive qualitative through a literature study involving books, journals, and other sources relevant to this study. The results show that the philosophy of Islamic education is an important foundation that shapes the direction, goals, and practices of Islamic education from the past to the future. In the past, Islamic education has proven capable of producing great scholars and scientists who played a role in building world civilization with a holistic education system, integrating religious knowledge and general knowledge. In the contemporary era, Islamic education faces various problems, such as a values ??crisis, weak character education, and challenges due to the strong currents of globalization, secularization, and technological developments. Meanwhile, in the future, Islamic education will be marked by increasingly complex global challenges, encompassing social, technological, and biological aspects. Therefore, Islamic education is required to be more progressive, adaptive, and creative in addressing the problems of the community, so that it remains relevant to current developments without losing the transcendental values ??of Islam.